1996
DOI: 10.1203/00006450-199608000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Regional Blood Flow and the Endocrine Response to Sustained Hypoxemia in the Preterm Ovine Fetus

Abstract: To determine the circulatory response of the preterm fetus to a sustained hypoxic insult, regional blood flow was measured (microsphere technique) in 12 unanesthetized fetal sheep (0.75 gestation) during a normoxic control period, after 1 h and 8 h of sustained hypoxemia, and after a 1-h recovery period. Associated endocrine changes which might relate to organ-specific changes in blood flow were also assessed. Myocardial and cerebral blood flow were increased by 240 and 90%, respectively, such that oxygen deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 14 publications
2
23
1
Order By: Relevance
“…The effect may be the result of circulating catecholamines and local factors such as nitric oxide and adenosine released during the hypoxia period and the immediate posthypoxic period. Recently, a similar response was reported in the sheep fetus at 75% of gestation 1 h after an 8 h period of hypoxia (Richardson, Korkola, Asano, Challis, Polk & Fraser 1996), in that heart rate and carcass blood flow were increased compared with baseline. They did not find increased blood flow to the brain.…”
Section: Co Distribution After Reoxygenationmentioning
confidence: 55%
“…The effect may be the result of circulating catecholamines and local factors such as nitric oxide and adenosine released during the hypoxia period and the immediate posthypoxic period. Recently, a similar response was reported in the sheep fetus at 75% of gestation 1 h after an 8 h period of hypoxia (Richardson, Korkola, Asano, Challis, Polk & Fraser 1996), in that heart rate and carcass blood flow were increased compared with baseline. They did not find increased blood flow to the brain.…”
Section: Co Distribution After Reoxygenationmentioning
confidence: 55%
“…Release of epinephrine (E) into the fetal circulation opposes vagal tone and returns FHR to basal levels (10). The fetal peripheral vasoconstriction is maintained by increased release of vasoactive agents into the fetal circulation, such as catecholamines, neuropeptide Y (NPY), and AVP (1,8,20,27,50,51,55,56,59).Although the cardiovascular responses to acute hypoxemia or asphyxia are known to change between mid and late gestation (7,30,33,34,64,65), no study has investigated developmental changes in cardiovascular responses to hy- …”
mentioning
confidence: 99%
“…Release of epinephrine (E) into the fetal circulation opposes vagal tone and returns FHR to basal levels (10). The fetal peripheral vasoconstriction is maintained by increased release of vasoactive agents into the fetal circulation, such as catecholamines, neuropeptide Y (NPY), and AVP (1,8,20,27,50,51,55,56,59).…”
mentioning
confidence: 99%
“…Persistent hypoxemia produces a redistribution of fetal cardiac output, which in turn is thought to result in asymmetrical fetal growth patterns. Richardson et al (1996) reported that redistribution effects in response to a sustained hypoxic insult (8 h) were qualitatively similar for both preterm and nearterm ovine fetuses. To sustain this redistribution, peripheral vasoconstriction in the fetus must be essentially maintained by sustaining hormonal effects.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few studies (Akagi and Challis 1990b;Carter et al 1998;Iwamoto et al 1989;Matsuda et al 1992;Richardson et al 1996) have been conducted in fetal sheep or goats at such early stages of development. We investigated fetal responses to sustained hypoxemia with pO 2 values around 15 mmHg for a duration of 24 h. Continuous infusion of nitrogen through the maternal tracheal catheter allowed us to rapidly and accurately adjust fetal pO 2 to the desired level.…”
Section: Discussionmentioning
confidence: 99%